Tapered active fiber simultaneously enabled 141 W high average and 1.3 MW high peak power via all-fiber and polarization-maintained picosecond amplifier. (August 2022) - Li, Wei; Ma, Pengfei; Lai, Wenchang; Song, Jiaxin; Wang, Tao; Ren, Bo; Liu, Wei; Zhou, Pu; Si, Lei
Highlights: An average output power of 141 W and peak power of 1.4 MW pulse laser is achieved with 3.4 ps pulse width. The polarization extinction ratio (PER) and beam quality (M 2 factor) are measured to be ∼16 dB and 1.19, respectively. By carefully adjusting the input signal power, the ASE and the SRS were effectively balanced. Abstract: An all-fiber and polarization-maintained (PM) picosecond pulses laser system is demonstrated based on tapered active fiber, which simultaneously enables high average and peak power. By carefully adjusting the input signal power and combining the advantages of tapered active fiber for high power scaling, the amplified spontaneous emission (ASE) and the stimulate Raman scattering (SRS) are effectively balanced and suppressed. An average output power of 141 W and peak power of ∼1.3 MW pulse laser is achieved with 3.4 ps pulse width at the repetition rate of 30 MHz. The polarization extinction ratio (PER) and beam quality (M 2 factor) are measured to be ∼16 dB and 1.19, respectively. As far as we know, this is the first demonstration of all-fiberized picosecond fiber source beyond megawatt (MW) peak power and hectowatt-level average power along with linear polarization and near-diffraction-limited beam quality.